MODELLING THE FACTORS AFFECTING CUSTOMERS’ INTENTION TO USE ARTIFICIAL INTELLIGENCE POWERED CHATBOT SERVICES IN BANKS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Indian banks are using AI-powered chatbots to  provide better customer service through real time communication and problem-solving. This  research study aims to compare customer intent  in using chatbot services offered by private and  public sector banks. Additionally, the study  investigates the significant factors that explain  customer behavioral intent to use AI-powered  chatbot services. The paper collected primary  data from Indian public and private sector bank  customers in Delhi-NCR through Google form  links, Instagram, and Facebook. The Unified  Theory of Acceptance and Use of Technology  (UTAUT) 2 was assessed, and statistical tools  such as paired sample t-tests and multiple  regression were used to test the hypotheses. The  results of the multiple regression analysis showed  that hedonic motivation plays a significant role  in understanding the intent of public sector  customers to use chatbots, while habit plays  a significant role for private bank customers.  The authors observed a significant difference  between public sector bank customers and  private bank customers in terms of behavioral  intent to use chatbot services, concluding that  private bank customers are more intent on using  chatbots compared to public sector customers.
Keywords: Chatbots and artificial intelligence have been subjects of interest and discussion due to their perceived complexity; Technological anxiety; risk; and social influence